Concertina Reforms with International Capital Mobility - Udo Kreickemeier; Pascalis Raimondos-Møller (Copenhagen Business School (CBS), Department of Economics, 2006)
We show that the standard concertina result for tariff reforms – i.e. lowering the highest tariff increases welfare – no longer holds in general if we allow for international capital mobility. The result can break down if the good whose tariff is lowered is not capital intensive. If the concertina reform lowers welfare it lowers market access as well, thereby compromising a second goal that is typically connected with trade liberalisation.
hdl:10398/7637
Keywords: F11; F13; F15; 330; Trade Policy Reform; International Factor Mobility; Welfare; Market Access